A Preliminary Study of Computed Tomography Coronary Angiography Within a Single Cardiac Cycle in Patients With Atrial Fibrillation Using 256-Row Detector Computed Tomography - Wen, B.; Xu, L.; Fan, Z.; Liang, J.; Sun, Zhonghua (LWW Business Offices, 2018)
Objective: The purpose of this study was to evaluate the image quality and radiation dose of computed tomography (CT) coronary angiography using a 256-row detector CT scanner in a single cardiac cycle in patients with atrial fibrillation (AF). Methods: Seventy consecutive patients (41 men and 29 women; age rangewas from 37 to 84 years, mean agewas 61.7 ± 10.2 years; bodymass index range was from 15.08 to 36.45 kg/m2, mean body mass index was 25.9 ± 3.5 kg/m2) with persistent or paroxysmal AF during acquisition, who were not receiving any medications for heart rate (HR) regulation, were imaged with a 256-row detector CT scanner (Revolution CT, GE healthcare). According to the HR or HR variability (HRV) the patientswere divided into 4 groups: group A (HR, =75 bpm; n = 36), group B (HR, <75 bpm; n = 34), group C (HRV, =50 bpm; n = 26), and group D (HRV, <50 bpm; n = 44). The snapshot freeze algorithm reconstruction was used to reduce motion artifactswhenever necessary. Two experienced radiologists, who were blinded to the electrocardiograph and reconstruction information, independently graded the CT images in terms of visibility and artifacts with a 4-grade rating scale (1, excellent; 2, good; 3, poor; 4, insufficient) using the 18-segment model. Subjective image quality scores and effective dose (ED) were calculated and compared between these groups. Results: The HR during acquisition ranged from 47 to 222 bpm (88.24 ± 36.80 bpm). A total of 917 in 936 coronary artery segments were rated as diagnostically evaluable (98.2 ± 0.04%). There was no significant linear correlation between mean image quality and HR or HRV (P > 0.05). Snapshot freeze reconstruction technique was applied in 28 patients to reduce motion artifacts and thus showed image quality was improved from 93.2% to 98.4%. The ED was 3.05 ± 2.23 mSv (0.49–11.86 mSv) for all patients, and 3.76 ± 2.22 mSv (0.92–11.17 mSv), 2.30 ± 2.02 mSv (0.49–11.86 mSv), 3.89 ± 2.35 mSv (1.18–11.86mSv), and 2.56 ± 2.03mSv (0.49–11.17 mSv) for groups A, B, C, and D, respectively. There were significant differences in mean ED between groups A and B, as well as C and D (P <0.05). Conclusions: This study shows that CT coronary angiography with use of a new 256-row detector CT in single cardiac cycle achieves diagnostic image quality but with lower radiation dose in patients with AF. Heart rate or HRV has no significant effect on image quality.